Biomass Gasification Potential for Slovenia’s Green Transition: E-Mobility - Hadžiselimović, Neja; Hadžiselimović, Tjaž (Journal of Energy Technology, 2025)
In 2024, approximately fifty percent of the total kilometers driven by passenger vehicles in Slovenia were attributed to diesel-powered automobiles, underscoring the persistent dependence of the transportation sector on fossil fuels, which are major contributors to greenhouse gas emissions and global warming. Research further substantiates that the transportation sector constitutes the nation's predominant source of greenhouse gas emissions. In this context, e-mobility emerges as a key strategy for Slovenia’s green transition in transportation. Additionally, biomass gasification represents a sustainable and environmentally friendly energy pathway that could support the country in achieving its environmental targets, while promoting the principles of the circular economy.